INTEGRATED CURRICULUM USED IN LEARNING ENGLISH - Marleni Marleni; Aswadi Jaya; Ferri Hidayad (Esteem Journal of English Education Study Programme, 2022)
In Indonesia, curriculum changes continue to occur because they are deemed not in accordance with expectations, so some schools apply the international curriculum. The Cambridge curriculum focuses on students' understanding, knowledge and critical thinking skills. This study aims to determine students' perceptions toward Cambridge curriculum used in learning English at Senior High School Sumsel, because students are the subject of implementing the curriculum. To find out the perceptions of students, researchers first studied how schools implemented the curriculum and the data analysis methods used were triangulation techniques, interviews to find out how the curriculum was implemented, questionnaires to determine student perceptions and documentation to support research results. The results of this study are (1) positive student perceptions. Positive things are shown by some students who are enthusiastic in learning to use the Cambridge curriculum and make students have a global prespective, (2) the implementation of the Cambridge curriculum in South Sumatra is quite good because schools continue to map the national curriculum and Cambridge curriculum and to material that is not the same will be made into additional class.